Ruling on the Rationalization of Consumption in Islamic Jurisprudence - Abdulkareem Hameed AL-jhayyish, Basim (International Journal of Psychosocial Rehabilitation, 2020)
Money is one of the necessities and the general purposes of Islamic law . God Almighty has put money legislation in place that ensures the achievement of financial interests, how to make money and dispose of it, and where to spend the money. Whoever follows this legislation gets the best of this world and the hereafter, and from the objection to this legislation, his money has become evil to him.